CHEMICAL PROPERTIES OF PELLETS OF Pinus sp. TORREFIED IN A SCREW TYPE REACTOR - Magalhães, Mateus Alves de; Carneiro, Angélica de Cássia Oliveira; Vital, Benedito Rocha; Silva, Carlos Miguel Simões da; Costa, Emylle Veloso Santos; Trugilho, Paulo Fernando (Floresta, 2018)
The combination of pelletization and torrefaction allows for obtaining pellets with higher energetic density. Thus, biomass becomes more attractive and usable for energetic purposes, and therefore, knowing the chemical properties becomes important to guarantee the quality of the torrefied pellets for fuel. The objective of this study was to evaluate the effect of torrefaction of Pinus sp. pellets on their chemical properties. The wood was previously transformed into particles and dried to 16% moisture content for further pelleting. For the torrefaction, the pellets were dried to 0% moisture content and subjected to heat treatment in a screw type reactor at the temperatures of 210, 250, and 290 °C and the times of 10, 20, and 30 minutes. In order to determine the chemical properties, the structural chemical composition, immediate chemical composition, elemental composition, and thermogravimetric analysis were performed. The torrefaction promoted significant changes in the chemical properties of Pinus sp. pellets, especially regarding the proportional increase of carbon content in detriment to oxygen reduction, increase of the thermal stability, and proportional increase of the lignin content by the reduction of the hemicelluloses. This improves the energetic quality of the biomass and turns it into a more competitive fuel when compared to fossil fuels.